The Association between Fishermen Status and Food Security of Fishermen Families in the West Aceh District - Wardah Iskandar; Rizki Maulidya; Ishalyadi Ishalyadi (Journal of Nutrition Science, 2020)
Fishermen are one of the livelihoods of the people in Indonesia, they depend on sea products, referring to development priorities in improving the quality of people and society that produce superior Indonesian humans, of course, also determined by adequate nutrition and nutritional adequacy is largely determined by food security in a family. The purpose of this study to determine the association between status of fishermen with food security in fishing families in the district West Aceh. This research method uses a cross-sectional study. The sample in this study amounted to 122 fishing families. Data collection was carried out by means of direct interviews covering the status of fishermen and food security, data analysis included univariate analysis, bivariate with independent sample t-test, and multivariate regression analysis. The results of research on 122 fishing families known that 56.25% of fishermen families who have capital have good food security, while 90.48% of laboring fishing families have poor food security. Bivariate analysis shows the variable of food security, with the status of fishermen having a value of P<0.05 which can be assumed that there is a significant difference between food security and the status of fishermen.